2022
DOI: 10.3390/diagnostics12092198
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Ischemic Mechanisms of Early Pressure Injury during Post-Decompression and Detecting Methods

Abstract: Background: Pressure injuries (PIs) generally result from prolonged ischemia through localized skin compression, and ischemia persists and exacerbates damage even post-decompression. The mechanisms of ischemia post-decompression are still unclear, and appropriate methods for detection are lacking. Methods: We used blanchable erythema (BE) and early PI rat models. We assessed the perfusion using Evans Blue (EB) and thrombus formation under a light microscope. Furthermore, we performed a capillary refill time te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 19 publications
(33 reference statements)
2
7
0
Order By: Relevance
“…Our study showed that progression to ulceration also takes more than 36 h. During this process, multiple circulatory disorders are involved and interact with each other. As is shown in Figure 9, recent studies have revealed that, in addition to the above-mentioned hemorrhage and hyperemia, congestion and ischemia are also found within lesions [8,9] . Furthermore, hemorrhage is a pathology that comes afterwards, so testing methods prior to hemorrhage, including the transparent disc method, are rarely mentioned.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our study showed that progression to ulceration also takes more than 36 h. During this process, multiple circulatory disorders are involved and interact with each other. As is shown in Figure 9, recent studies have revealed that, in addition to the above-mentioned hemorrhage and hyperemia, congestion and ischemia are also found within lesions [8,9] . Furthermore, hemorrhage is a pathology that comes afterwards, so testing methods prior to hemorrhage, including the transparent disc method, are rarely mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…The wound area of the rats was placed on a round platform (2 cm in diameter) and then compressed. As described previously [9], the pressure applied in the current study was set at 150 mmHg. The pressure instrument used an electric stand (MX500N; Imada Co., Toyohashi, Japan) to regulate the pressure.…”
Section: Measurement Of Ischemia-the Transparent Disc Methods and Crttmentioning
confidence: 99%
See 3 more Smart Citations